Inequality of Arabic Subjects in the General Education Curriculum in Indonesia - Rahmap, Rahmap; Yani, Achmad; Ishak, Midyan Surya (Institut Agama Islam Negeri Curup, 2024)
The objectives of this study are 1) to describe the fact of inequality of Arabic subjects in the curriculum as a compulsory subject at the upper secondary education level, 2) to determine the inequality factors of Arabic subjects in the general education curriculum, and 3) to determine the implications of inequality in Arabic as the main subject. Graduates of general education who proceed to Islamic religious universities often encounter challenges in mastering Arabic. This may occur due to the absence of Arabic language subjects during their high school years, compounded by Arabic not being a mandatory component of the general education curriculum. This research uses a qualitative approach with a descriptive research method. Data collection techniques include literature studies, and data analysis used are content analysis. The findings indicate that Arabic is not designated as a core subject in the national education curriculum for secondary education, highlighting the unequal treatment of Arabic within the Indonesian education system. This disparity's repercussion is evident in the challenges encountered by high school graduates when pursuing Arabic studies at Islamic Religious Colleges, stemming from struggles in grasping the fundamentals of the Arabic language. Arabic language learning in general education is only an elective subject in private schools affiliated with religious organizations. This results in students facing challenges in acquiring knowledge in Arabic and grappling with the complexities of learning Islam, particularly for Muslim students.